Fuzzy Logic Based MPPT Control and Automated Battery Management System for Improved Performance of Micro Grid - B. Ganga Raju, B. V. Sankar Ram (International Journal of Control and Automation, 2020)
The utilization of renewable energy sources has been increasing from the last few years due to their enormous advantages. This paper presents design of the Microgrid system based up on the renewable energy sources like solar and wind. Also due to advantages of the fuel cell power generation, it has been used as another source for the micro grid system. A multi input single output high gain dc to dc boost converter has been using which boost up the voltages of all the three sources and generates single output energy. A three level inverter has been using for converting DC step up voltage into AC voltage for supplying the AC load. Also battery has been used for storing the energy and supplies to the load when there is no enough supply from the sources. So battery management system has been designed which directs flow of energy into the battery based up on the load and sources supply conditions. This paper also involves the design and comparison of Maximum power point tracking (MPPT) system with different types of controllers like PID Controller and fuzzy controller. The entire system has been simulated using MATLAB Simulink and results are verified.